A Novel Curriculum on Using Life Expectancy to Inform Cancer Screening in Older Adults. Issue 2 (4th January 2021) - Ahmed, Shaista U.; Burke, Meg; McGuire, Maura; Massare, Jacqueline; Boyd, Cynthia M.; Pollack, Craig E.; Lentz, Caroline; Schoenborn, Nancy L.
Abstract : Background: Many older adults with limited life expectancy still receive cancer screening. One potential contributor is that primary care providers (PCP) are not trained to incorporate life expectancy in cancer screening recommendations. We describe the development and evaluation of a novel curriculum to address this need. Methods: We developed and implemented a web‐based learning module within a large Maryland group practice with PCPs for older adults. We assessed attitude, knowledge, self‐efficacy, and self‐reported behavior outcomes before the module, immediately after completing the module, and 6 months afterwards. Results: Of 172 PCPs who were invited, 86 (50%) completed the module and of these, 50 (58.1%) completed the 6‐months follow up survey. Immediately after the module, there was a significant increase in perceived importance of life expectancy (increase of 0.50 point on 10‐point scale, 95% confidence intervals (CI) = 0.27–0.73), confidence in predicting life expectancy (increase of 2.32 points on 10‐point scale, 95% CI = 1.95–2.70) and confidence in discussion screening cessation (increase of 1.69 points on 10‐point scale, 95% CI = 1.37–2.02). Knowledge in patient‐preferred communication strategies improved from 55% correct response to 97% ( P < .001). However, most of these improvements dissipated by 6 months and there was no change in self‐reported behavior at 6 months compared to baseline ( P = .34). Conclusion: Although the module resulted in significant short‐term improvement in attitude, knowledge, and self‐efficacy, the changes were not sustained over time. Educational interventions such as this can be coupled with ongoing reinforcing strategies and/or decision support interventions to improve cancer‐screening practices in older adults.